2007
DOI: 10.1007/s10267-007-0384-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carbohydrate substrate on the vegetative mycelial growth of an ectomycorrhizal mushroom, Tricholoma matsutake, isolated from Quercus

Abstract: We studied the characteristics of the utilization of carbohydrate substrates and the production of those hydrolyzing enzymes of the Tricholoma matsutake J-1 strain isolated from hardwood (Quercus sp.). In the culture medium, 5% glucose inhibited mycelial growth. The growth inhibition rate was remarkable in the Z-1 strain from softwood (Pinus densifl ora) compared with that of the J-1 strain from hardwood. α-Amylase production varied with starches from different origins in contrast to mycelial growth. The range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…This phenomenon can be explained by two ways: (i) the mycelial catabolism was suppressed by the higher concentration of nutrients because of osmotic pressure as the ectomycorrhizal fungi do not grow under high osmotic pressure and (ii) presence of high concentration of vitamin and hormones increased the activity of some enzymes which could suppress mycelial growth [23,24]. These kinds of effect were also reported from other scientists with the application of carbohydrate components [25,26]. It was found that higher concentration of extra glucose had an effect on catabolite suppression in the ECM fungal group.…”
Section: Discussionmentioning
confidence: 66%
“…This phenomenon can be explained by two ways: (i) the mycelial catabolism was suppressed by the higher concentration of nutrients because of osmotic pressure as the ectomycorrhizal fungi do not grow under high osmotic pressure and (ii) presence of high concentration of vitamin and hormones increased the activity of some enzymes which could suppress mycelial growth [23,24]. These kinds of effect were also reported from other scientists with the application of carbohydrate components [25,26]. It was found that higher concentration of extra glucose had an effect on catabolite suppression in the ECM fungal group.…”
Section: Discussionmentioning
confidence: 66%
“…Therefore, only glucose and some other monosaccharides and disaccharides can be used for growth (Kusuda et al, 2007). It is possible that the low glucose level in the MMN medium (10 g·liter -1 ) was the reason the mycelium grew less, because, as reported by Hatakeyama and Ohmasa (2004a) El PDA fue el mejor medio de cultivo.…”
Section: Resultados Y Discusiónmentioning
confidence: 97%
“…Por tanto, únicamente la glucosa y algunos otros monosacáridos y disacáridos pueden utilizarse para el crecimiento (Kusuda et al, 2007). Es posible que el bajo contenido de glucosa en el medio MNM (10 g·litro -1 ) fue la causa de que el micelio creciera menos pues, según lo reportado por Hatakeyama y Ohmasa (2004a), muchas cepas de Suillus y Boletinus crecieron mejor en concentraciones relativamente altas de glucosa (3.33 a 10 %), como es el caso del medio BAF (30 g·litro -1 ), mientras que el crecimiento de otras especies se inhibió a esta concentración (Hakateyaa & Ohmasa, 2004b).…”
Section: Resultados Y Discusiónunclassified
“…From the results of our experimental series studying L. shimeji (Kusuda et al 2004) and T. matsutake (Terashita et al 1995(Terashita et al , 2000Kusuda et al 2003Kusuda et al , 2006Kusuda et al , 2007, we drew a fi gure summarizing the carbohydrase production of the ectomycorrhizal mushrooms L. shimeji and T. matsutake, and we pointed out the weak points of the artifi cial cultivation of T. matsutake (Fig. 4).…”
Section: Discussionmentioning
confidence: 97%